Prevalence and characteristics of talon cusps in Turkish population - Yeliz Guven; Yelda Kasimoglu; Elif Bahar Tuna; Koray Gencay; Oya Aktoren (Wolters Kluwer Medknow Publications, 2016)
Background: Talon cusp is a rare dental anomaly characterized by a cusp-like projection, often including the palatal surface of the affected tooth. The aim of the present study was to investigate the prevalence and characteristics of talon cusps in a group of Turkish children. Materials and Methods: The study population consisted of 14,400 subjects who attended the clinics of the Department of Pediatric Dentistry at the Istanbul University, Istanbul, Turkey . Subjects ranged in age from 1 to 14 years with a mean age of 10.5 ± 2.55 years. Talon cusps were mainly categorized by visual examination according to the classification of Hattab et al. The distribution and frequency of talon cusps were calculated with respect to dentition type, tooth type, talon type, the affected surface, associated dental anomalies, and clinical complications. Statistical analysis included descriptive statistics, frequencies, and crosstabs with Chi-square analysis. Results: Talon cusps were detected in 49 subjects (26 males and 23 females) of 14,400 (0.34%). A total of 108 teeth showed talon cusps. Distribution of talon cusps according to gender showed no statistically significant differences. The incidence of talon cusps was found to be greater in maxillary lateral incisors (53.7%) than central incisors (29.62%). Regarding the type of talon cusp, 47.22% of teeth showed a Type III talon cusp, whereas 30.55% of teeth demonstrated a Type II talon and 22.22% of teeth demonstrated a Type I talon cusp. Nine patients (18.36%) with talon cups also exhibited other developmental dental anomalies. Clinical complications associated with talon cusps were detected as caries formation and occlusal interference. Conclusion: This is the most comprehensive study of the prevalence of talon cusps in Turkish population using the largest sample size to date. Also, taurodontism associated with a talon cusp has been reported here for the 1 st time. Clinical complications associated with talon cusps need more investigations.